Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1037/0021-843x.105.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite structure of positive and negative affect, depression, and anxiety in child and adolescent psychiatric inpatients.

Abstract: The tripartite model of depression and anxiety suggests that depression and anxiety have shared (generalized negative affect) and specific (anhedonia and physiological hyperarousal) components. In one of the 1st studies to examine the structure of mood-related symptoms in youngsters, this model was tested among 116 child and adolescent psychiatric inpatients, ages 8-16 (M = 12.46; SD = 2.33). Consistent with the tripartite model, a 3-factor (Depression, Anxiety, and Negative Affect) model represented the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
255
2
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(281 citation statements)
references
References 36 publications
18
255
2
6
Order By: Relevance
“…The negative affect scale of the PANAS-C demonstrates good internal consistency (e.g., α = .91 in the present sample), as well as adequate discriminant and convergent validity (Joiner et al, 1996).…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…The negative affect scale of the PANAS-C demonstrates good internal consistency (e.g., α = .91 in the present sample), as well as adequate discriminant and convergent validity (Joiner et al, 1996).…”
Section: Methodsmentioning
confidence: 58%
“…Replication of the current findings and continued refinement of measuring AS among youth would strengthen confidence in the current findings. (Joiner et al, 1996); CASI = Childhood Anxiety Sensitivity Index (Silverman et al, 1991); AS-DC = Anxiety Sensitivity -Disease Concerns; AS-UC = Anxiety Sensitivity -Unsteady Concerns; AS-MI = Anxiety Sensitivity -Mental Incapacitation Concerns; AS-SC = Anxiety Sensitivity -Social Concerns; Posttraumatic Stress Symptoms were indexed using the CPSS (Foa et al, 2001). .01…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CDI is probably the most commonly used measure of assessing depressive symptoms among youth, its construct validity and specificity as a measure of depression has been questioned (e.g., Chorpita et al 2005;King et al 1991) given that it appears to contain many items tapping broad negative affect (Chorpita et al 1998). Thus, although the CDI was intended to assess the depressive symptoms factor of the hierarchical model of internalizing problems Watson 2005) given its wide-spread use, the questionable specificity and construct validity led to the decision to select particular anhedonia items from the CDI, based on past work (e.g., Chorpita et al 1998;Joiner et al 1996) in order to examine both the full CDI as the commonly used measure of general depressive symptoms and the relatively more specific anhedonic depressive symptoms based on the CDI. In sum, analyses for depressive symptom specificity are reported for the full CDI to assess general depressive symptoms and for anhedonic CDI items (nos.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies in clinical and community samples of adults and children (e.g. Clark et al 1994;Watson et al 1995;Joiner et al 1996;Brown et al 1998;Chorpita & Daleiden, 2002) have reported that depressed and anxious participants exhibit the predicted differences in positive affectivity and physiological arousal, but are similar with respect to negative affectivity.…”
Section: Introductionmentioning
confidence: 99%